The Analysis of the Knowledge -Based Leadership Relationship, Knowledge Management Behavior and Innovation Performance (Case Study: Small and Medium Companies of Chaharmahal & Bakhtiari Province) - meysam babaee farsani; soheila fathollahi; mina Moradi (مدیریت راهبردی دانش سازمانی, 2022)
The purpose of the present study was to investigate the analysis of knowledge-based leadership relationship, knowledge management behavior, and innovation performance in small and medium-sized companies in Chaharmahal and Bakhtiari province by modifying staff orientation. The present study was correlation in terms of correlation and purpose. The research tool is based on Donat and Pablod’s standard Questionnaires (2015), Jang et al. (2017), Shamim et al. (A2017) and Sojan et al. (19940) After measuring validity (Fornel and Lockers’s convergent and divergent) and Reliability (Cronbach's alpha, Combined and Dystra), through the participation of 140 small and medium - The data analysis method was implemented at two descriptive and inferential levels through SPSS25 and Warppls8 software. The results showed that knowledge-based leadership had a significant impact on all aspects of knowledge management behavior (business, transfer, documentation, and application). The findings also showed that knowledge-based leadership has influenced innovation performance through all aspects of knowledge management behavior. Ultimately, the target orientation of employees has been able to adjust the relationship between knowledge-based leadership and knowledge documentation as well as knowledge application.